The Affordable Care Act and Its Impact on Plastic and Gender-Affirmation Surgery. Issue 1 (24th December 2020) - Wiegmann, Aaron L.; Young, Ezra I.; Baker, Kellan E.; Khalid, Syed I.; Seu, Michelle; Shenaq, Deana S.; Dorafshar, Amir H.; Schechter, Loren S.
Abstract : Summary: The Affordable Care Act's provisions have affected and will continue to affect plastic surgeons and their patients, and an understanding of its influence on the current American health care system is essential. The law's impact on pediatric plastic surgery, craniofacial surgery, and breast reconstruction is well documented. In addition, gender-affirmation surgery has seen exponential growth, largely because of expanded insurance coverage through the protections afforded to transgender individuals by the Affordable Care Act. As gender-affirming surgery continues to grow, plastic surgeons have the opportunity to adapt and diversify their practices.